Laser-induced Pain for Quantitative Comparison of Intravenous Regional Anesthesia Using Saline, Morphine, Lidocaine, or Prilocaine. Issue 4 (July 1990) - Arendt-Nielsen, Lars; Oberg, Bjarne; Bjerring, Peter
Abstract : The significance of ischemia-producing intravenous regional anesthesia (IVRA) was investigated using isotonic saline for injection. The possible analgesic effect of morphine was tested by injecting 40 ml morphine hydrochloride 0.01% for IVRA. Analgesia was evaluated subjectively by measuring the thresholds (warmth and pain) to laser stimulation and objectively by measuring the brain potentials (amplitude and latency) evoked by brief laser stimuli. Morphine and saline produced total pain alleviation after 30 minutes of IVRA. A control study was performed in which 40 ml lidocaine 0.5% and 40 ml prilocaine 0.5% were used for IVRA. This caused an inhibition of the laser-induced pain after 5-10 minutes. After the deflation of the cuff, the thresholds and the brain potentials recovered rapidly. No differences in the efficacy of lidocaine or prilocaine were observed. It is concluded that 30 minutes of tourniquet application is sufficient to cause analgesia and that morphine does not provide more adequate analgesia than saline when used for IVRA.